Surprise Marketing sebagai Strategi Membangun Customer Engagement: Studi Konseptual pada Implementasi POP MART - Sri Yuliyanti; Ahmad Fadhli; Fita Yunitasari (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
Digital consumer behavior requires companies to design marketing strategies that go beyond product selling and create meaningful customer experiences. This article develops a conceptual understanding of Surprise Marketing as a strategy for building Customer Engagement in the context of POP MART. The study adopts a conceptual paper approach using a Narrative Literature Review by synthesizing literature on Surprise Marketing, Information Gap Theory, Consumer Curiosity, Customer Experience, Emotional Experience, Customer Engagement, blind box consumption, Repurchase Intention, Electronic Word-of-Mouth (e-WOM), and competitive advantage. The reviewed literature was selected based on its theoretical relevance and its contribution to explaining the relationship between surprise-based marketing strategies and consumer behavioral outcomes in digital environments. The review indicates that POP MART implements Surprise Marketing through blind boxes, secret editions, limited editions, recurring product launches, and the unboxing experience. These elements create an information gap that stimulates consumer curiosity, generates emotional experience, and strengthens Customer Engagement across cognitive, emotional, and behavioral dimensions. The synthesis also demonstrates that emotional attachment formed through repeated surprise experiences reinforces consumers' willingness to interact continuously with the brand and participate in online brand communities. Customer Engagement then leads to repurchase intention, e-WOM, collector communities, and stronger differentiation. POP MART annual reports are used as supporting evidence showing that experience-based marketing is relevant to business growth and international expansion. This article contributes to the marketing literature by proposing a conceptual framework that positions Customer Engagement as the key mechanism connecting Surprise Marketing with marketing outcomes. The proposed framework is expected to provide a theoretical basis for future empirical research investigating the effectiveness of Surprise Marketing in enhancing customer engagement across various digital consumer markets.